Ethnobotany of Natural Dye Plants of Godhongkoe and Cindelaras for Eco-Friendly Ecoprint Batik in Surakarta - Devi Septiana Putri; Siswo Aji Prasetyo; Nurmiyati Nurmiyati; Joko Ariyanto (Jurnal Biologi Tropis, 2026)
The demand for environmentally friendly textiles has driven the increasing use of plant-based natural dyes, particularly in ecoprint batik products. However, local knowledge regarding dye plant species, utilized plant parts, and dyeing techniques has not been systematically documented. This study aims to examine the utilization of natural dye plants in ecoprint batik fabric production within the GodhongKoe and Cindelaras communities in Surakarta City, Central Java. The research employed a descriptive method using primary data obtained through observations, questionnaires, and interviews with artisans selected through purposive sampling. Data were analyzed qualitatively and quantitatively by calculating the percentage of plant organ usage. The results showed that both communities utilized 10 plant species each. Leaves were the most dominantly used plant organ, accounting for 60% of total usage, due to their easy availability and effectiveness in producing natural patterns and colors. In addition, stems and bark were utilized as sources of strong pigments and natural fixatives. This study concludes that ecoprint practices reflect the utilization of local plant diversity based on ethnobotanical knowledge. These findings contribute to the preservation of local knowledge on the use of natural dye plants while supporting the development of environmentally friendly creative industries based on local biological resources.